Recent findings from the Upper Limb Consortium Study: new approaches to risk assessment and additional health outcomes. (November 2019) - Harris, Carisa; Rempel, David; Meyers, Alysha R; Bao, Stephen; Kapellusch, Jay; Rempel, David; Harris, Carisa
Historically, work-related upper-extremity musculoskeletal disorders (MSD) have comprised a significant portion of the number and cost of injuries in the workplace. The problem of work-related upper-extremity MSD has been, and continues to be, widespread and costly. This panel will present recent research from the Upper Extremity Musculoskeletal Consortium studies. Presentations will be made on new health outcomes such as wrist tendinosis, epicondylitis and rotator cuff syndrome, as well as provide updates on applying new risk assessment methods to prior analyses. The application of the Revised Strain Index will be presented as will a comparison of results from the 2001 ACGIH TLV for Hand Activity to the 2018 ACGIH TLV for Hand Activity. Additionally, the impact of healthy worker survivor effect on the pooled analyses of incident CTS and CTS related disability will be discussed.